Horror noir where cinema's dark sisters meet - Meehan, Paul, 1948- (McFarland & Co., Inc., Publishers, 2011)
"This critical survey examines the relationships between horror and film noir. Included are the films based on popular horror/mystery radio shows, the works of Val Lewton, and Alfred Hitchcock's stories. Also discussed are gothic and costume horror noirs; the noir of recent films; and film noir aspects of the Hannibal Lecter movies and other serial-killer thrillers"--Provided by publisher.